Corporate Social Responsibility as a part of Corporate Public Relations in Serbia - Vuković, Andrea; Mihić, Svetlana; Miletić, Ljiljana; Čurčić, Radmila (Industrija, 2016)
Besides the media, the web presentations of the companies are one of the possible and widely applied means for communication of corporate social responsibility (CSR). For efficient CSR communication, good planning of the massages that will be presented to the public is of particular importance. It is additionally emphasized in the countries in the transition period where the social environment is burdened with numerous problems that result in pre-formed public mistrust towards companies. The extent and the results of public cognition of the company and creation of its identity and image are highly dependent from content of the web presentation but also of the manner of presentation and positioning of specific contents. Application of adequate slogans, can also highly contribute to the visibility of specific information. In order to review the way in which companies in Serbia present their CSR motives and activities, the web pages of leading companies in Serbia from the agro-business, public and financial sectors were analyzed and the practice of presentation of CSR to the public was reviewed. The similarities and differences in approach to CSR communication among analyzed sectors are outlined in the research results.
Keywords: Web presentations; Public Relations; Corporate social responsibility; Communication